Case Report: Spontaneous Fetal Demises at Third Trimester of Pregnancy Due to a Double Lopped Nuchal Cord in Camelus dromedarius - Son, Young-Bum; Hossein, Mohammad Shamim; Yu, Xianfeng; Jeong, Yeon Ik; Olsson, P. Olof; Hwang, Woo Suk (Frontiers in Veterinary Science, 2022)
The umbilical cord acts as the critical lifeline of the developing fetus by providing nutrients and oxygen to it. Umbilical cord abnormalities are considered the leading cause of stillbirth in humans, but information rereading stillbirths associated with umbilical cord abnormalities are very scant in animals’ clinical practices. Here we described a case of fetal demises in camels indicated to be caused by fetal death from strangulation by its umbilical cord which is commonly known as the nuchal cord. A pregnant camel at its 36-weeks of gestation spontaneously aborted a single fetus. The camel was 5 years old and nullipara. A six-day-old cloned embryo was transferred transcervically to the recipient. The pregnancy was confirmed 50 days after embryo transfer by ultrasonography and pregnant camel was maintained under a standard nutritional plan. The neck of the aborted fetus was strangulated tightly by a double loop of the umbilical cord. There was no congenital anomaly or other malformation in the fetus. We concluded the nuchal cord was tightly coiled around the neck of the fetus which interfered the blood flow to the fetus by collapsing the umbilical vein and subsequently cause of fetal death and abortion. To the authors’ knowledge, this is the first reported case of a nuchal cord in camels.